Прочность скелета у животных с измененным характером опоры - Мельник, К.П. (Вестник зоологии, 1972)
An effect of different physical loading and a changed character of the support was studied as applied to mechanical properties, histological structure, mineralization degree and size of tubular bones in dog, domestic cat and rabbit limbs. It is established that when one of the limbs is eliminated as a support the physical loading for the limb of the other side increases. Skeletal elements of the unloaded limb are subjected to rearrangement accompanied by a relative decrease in their weight. Thick-ness of the diaphysis walls and the area of compact substance total destructing loading and ultimate strength of bony tissue also decrease. Mineral metabolism in skeletal ele-ments without a. support is disturbed and ash amount in them is reduced. Similar changes were observed when dynamic loadings in animals are absent.